Necrotizing Fasciitis and Methicillin Resistant Staphylococcus Aureus - W. Ninawe, Dr. Rima; Ninawe, Dr. Wasudeo Gyanidas (International Journal of Innovative Research in Medical Science, 2018)
Necrotizing fasciitis (NF) is an aggressive and life-threatening infection of skin and soft tissue characterized by widespread fascial necrosis which leads to morbidity and mortality if left untreated. There is difficulty in managing this condition because there is a combination of difficulty in diagnosis, and also of early as well as late management. It can be caused by either a single organism or more frequently by a variety of microbes - both aerobic and anaerobic. Necrotizing fasciitis seems to have preponderance in males, perhaps due to increased incidence of trauma in males. Staphylococcus aureus is the most prevalent pathogen in hospitals and communities and MRSA has become a common isolate associated with skin and soft tissue infections over the past few years, monomicrobial MRSA necrotizing fasciitis has been reported only in a few studies. Early surgical intervention, early diagnosis and aggressive treatment should be done. Material and Methods: All patients were diagnosed as NF on surgical report. Surgical exploration is undertaken after resuscitation. Penicillin along with, an amino glycoside and clindamycin or metronidazole is administered preoperatively in moribund patients. Cefoxitin or imipenem or meropenem is used in more limited infections. Fair amount of desloughing is done without anesthesia. Overlying fat as patchy greenish-black liquefaction necrotic tissues are excised primarily, and specimen sent for culture in microbiology department. Cultures were processed the susceptibility of S. aureus isolates to antimicrobials was done. Results: A total of 200 hospitalized patients those who were surgically treated for NF were included in the study. Of the 200 patients 42 patients were culture positive for MRSA. In our study mean age was 56± 11.21 of which 124 (62%) were male , mean hospitalization days were 16.5± 6.2. patients with underlying diabetes mellitus were 66 (33%) and hypertension were 74(37%). In MRSA group (n=42) mean age was 53 ± 9.22. Male were 36 (73.81%) , mean hospitalization days were 17.6 ± 6.2. patients with underlying diabetes mellitus were 21 (50%) and hypertension were 19(45.24%).42 (21%) were MRSA, 31 (15.5%) were MSSA, 21 (10.5%) were coagulase negative staphylococcus, 4(2%) were Streptococcus group A, 11 (5.5%) were Streptococcus species, 6 (3%) were Bacillus species, 24 (12 %) were Escherichia coli, 19 (9.5%) were Acinetobacter species, 3 (1.5%) were Candida albicans and in 30 (15%) no growth was observed in culture. Discussion and Conclusion: Some experts recommend use of broad-spectrum empirical antimicrobial therapy for suspected cases of necrotizing fasciitis and therapy directed against MRSA is not a standard practice. For treatment selection of appropriate antimicrobial agents for any suspected necrotizing fasciitis must take into account the nature of patient's exposure and local epidemiologic data but no reliable epidemiological or clinical risk factors with MRSA from those infected with MSSA or non-S. aureus are available. In our study mean age of patients diagnosed NF was 53 ± 9.22. While male were 36 (73.81%). In study by Cheng NC et al. the median age was 62 years (range, 12-81 years) There was male predominance in NF by MRSA in our study . In our study lesions on extremities had better prognosis similar results were shown in other study. Necrotizing fasciitis caused by MRSA is a challenge to the treating surgeon. Prompt diagnosis and surgical management with empiric MRSA cover in areas where community acquired MRSA (CA-MRSA) is endemic. Lesions of extremities have better prognosis where MRSA infection is becoming endemic and empirical treatment of suspected necrotizing fasciitis or pneumonia should include active MRSA cover.